Time dependent – density functional theory characterization of organic dyes for dye-sensitized solar cells. Issue 18 (12th December 2017) - Hilal, Rifaat; Aziz, Saadullah G.; Osman, Osman I.; Bredas, Jean-Luc
Abstract: We aim at providing better insight into the parameters that govern the intramolecular charge transfer (ICT) and photo-injection processes in dyes for dye-sensitised solar cells (DSSC). Density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations are utilized to study the geometry, electronic structure, electrostatic potential (ESP) and absorption spectrum, for a representative donor-π bridge-acceptor (D–π–A) dye for DSSC. The coplanar geometry of the dye (D1) facilitates strong conjugation and considerable delocalization originating the π CT interaction from donor to acceptor orbitals and the hyper-conjugative interactions involving Rydberg states. A model simulating the adsorption of the dye on the TiO2 surface is utilized to estimate binding energies. The effect of fluorine substituents in the π-spacer on the quantum efficiency of DSSCs was investigated. Gibb's free energy values, redox potentials, excited state lifetime, non-linear optical properties (NLO) and driving forces for D1 and its fluorinated derivatives were computed.